The Recovery of Platelet Malondialdehyde Production After a Single Intake of Aspirin - The Effect of Dosage - Takayama, Hiroshi; Okuma, Minoru; Uchino, Haruto (Thrombosis and Haemostasis, 1982)
We studied the recovery pattern of platelet malondialdehyde (MDA) formation after a single intake of various doses of aspirin (ASA). In normal subjects, there were striking differences in the recovery pattern between large doses (1,000 or 500 mg) and small doses (100 or 50 mg) of oral ASA. The 2 day lag phase was present in the large dose group which showed the complete inhibition of the circulating platelets 2 hr after oral ASA but not in the small dose group which showed the incomplete inhibition. The difference of recovery time between these two groups was about 2 days. These data suggest that ASA’s effect on megakaryocytes might affect the recovery pattern of MDA formation by the circulating platelets. In 2 patients with chronic idiopathic thrombocytopenic purpura, the 2 day lag phase was not observed in the recovery even after a large ASA dose.
Keywords: Platelet life span; Aspirin; Malondialdehyde; Thiobarbituric acid reaction; Megakaryocyte